Effect of Radial Stress on the Nanoparticle-Based Electrolyte Layer in a Center-Wound Roll with Roll-to-Roll Systems - Jaehyun Noh; Minho Jo; Gyoujin Cho; Sanghoon Nam; Changwoo Lee (Nanomaterials, 2022)
Recently, slot-die coating based on the roll-to-roll process has been actively used to fabricate nanoparticle-based electrolyte layers because it is advantageous for high-speed processes and mass production of uniformly thick electrolyte layers. In this process, the fabricated electrolyte layer is stored as a wound roll throughout the rewinding process. We analyzed the defects and geometric changes in an electrolyte layer, i.e., gadolinium-doped cerium oxide (GDC), due to the radial stress in the wound roll. We found that the thickness of the coated layer could be decreased by increasing the radial stress, i.e., cracks can be generated in the coated layer if excessively high radial stress is applied to the wound-coated layer. More thickness changes and crack defects were generated with time due to the residual stress in the wound roll. Finally, we analyzed the effects of taper tension profiles on the defects of the coated layer in the wound roll and determined the taper tension profile to minimize defects.